A projection-based approach to extend digital volume correlation for 4D spacetime measurements - Kosin, Viktor; Fau, Amélie; Jailin, Clément; Smaniotto, Benjamin; Wick, Thomas; Hild, François (Comptes Rendus. Mécanique)
In-situ (tomography) experiments are generally based on scans reconstructed from a large number of projections acquired under constant deformation of samples. Standard digital volume correlation (DVC) methods are based on a limited number of scans due to acquisition duration. They thus prevent analyses of time-dependent phenomena. In this paper, a modal procedure is proposed that allows time-dependent occurrences to be analyzed. It estimates spacetime displacement fields during the whole loading history. The spatial modes are based on standard DVC, which is subsequently enriched using projection-based digital volume correlation (P-DVC) to measure the temporal amplitudes. The method is applied to two cases, namely, a virtual experiment mimicking wedge splitting and an actual shear test on a pantographic metamaterial inducing large motions. With the proposed method, the temporal amplitude in the real test was measured for each projection leading to a temporal resolution of one tenth of a second and the analysis of 16,400 time steps. For the proposed algorithm, the sensitivity to the acquisition angle of the sample was investigated and measurement uncertainties were assessed.